Pastagens de capim elefante e azevém consorciadas com leguminosas - Diehl, Michelle Schalemberg (2015)
The objective of this study was to conduct analysis of data from six experiments with forage systems with Elephant Grass (EG) + Italian Ryegrass (IR) + Spontaneous Growing Species (SGS); EG + IR + SGS + Forage Peanut; and EG + IR + SGS + White or Red Clover, conducted in the Laboratório de Bovinocultura de Leite da Universidade Federal de Santa Maria, with rotational grazing using dairy cattle. The experiments analyzed were conducted between the years 2005 to 2013 and grouped by the month they grazing cycles were performed. Holstein dairy cows were used for evaluation, with an average body weight and milk production of 543 kg and 19 kg/day, respectively. The total forage production values and the average stocking rate and crude protein levels were 13.8, 16.5 and 16.8 t/ha; 2.90; 2.91 and 2.92 AU/ha/day and 17.5, 18.6 and 18.2%, for the respective forage systems. The forage systems consisting by forage legumes presented the best results in relation to pasture productivity and nutritive value of forage. The mixed with forage peanut controlled the spontaneous growing species and participated in the herbage mass throughout the year. In mixed pasture with clovers the nitrogen contribution to the system resulted in better conditions for the development of grasses forage (Italian ryegrass or elephant grass).